Concurrent exception handling and resolution in distributed object systems - Jie Xu; Romanovsky, A.; Randell, B. (IEEE transactions on parallel and distributed systems, 2000)
We address the problem of how to handle exceptions in distributed object systems. In a distributed computing environment, exceptions may be raised simultaneously in different processing nodes and thus need to be treated in a coordinated manner. Mishandling concurrent exceptions can lead to catastrophic consequences. We take two kinds of concurrency into account: 1) Several objects are designed collectively and invoked concurrently to achieve a global goal and 2) multiple objects (or object groups) that are designed independently compete for the same system resources. We propose a new distributed algorithm for resolving concurrent exceptions and show that the algorithm works correctly even in complex nested situations, and is an improvement over previous proposals in that it requires only O(n/sub max/N/sup 2/) messages, thereby permitting quicker response to exceptions.